2018
DOI: 10.1016/j.rmed.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral endothelial function is positively associated with maximal aerobic capacity in patients with chronic obstructive pulmonary disease

Abstract: Peripheral endothelial function was positively associated with maximal aerobic capacity, when correcting for sex, age and systolic blood pressure. Establishing peripheral endothelial dysfunction as a determinant of impaired aerobic capacity in COPD can be valuable for developing interventions aiming to improve aerobic capacity, and in turn cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
(99 reference statements)
1
11
0
Order By: Relevance
“…It is also important to point out that the current sample, in general, did not present endothelial dysfunction. Corroborating our findings, Vaes et al () did not found correlation between RHI and the 6MWT, but they found correlation with maximal aerobic capacity (VO 2 peak). However, that sample presented less severe airflow limitation and higher prevalence of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is also important to point out that the current sample, in general, did not present endothelial dysfunction. Corroborating our findings, Vaes et al () did not found correlation between RHI and the 6MWT, but they found correlation with maximal aerobic capacity (VO 2 peak). However, that sample presented less severe airflow limitation and higher prevalence of endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…Up to our knowledge, only two prior cross‐sectional studies assessed endothelial function (RHI), and only one AIx with PAT in patients with COPD (Minet et al, ; Vaes, Spruit, Theunis, Wouters, & De Boever, ). Minet et al () found a mean RHI of 0.43 ranging from −0.14 to 1.3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding COPD, the information is limited and conflicting. When the present study was designed, there were no prospective studies investigating the effect of exercise training programmes on endothelial function in COPD, and the evidence was based on retrospective analysis [ 8 , 15 ] showing that endothelial function was positively related to physical activity level and exercise capacity. While this study was ongoing, one prospective study was published by G elinas et al .…”
mentioning
confidence: 99%
“…Clarenbach et al showed that patients with severe airflow obstruction who were physically active were less prone to more severe impairments of FMD, compared to inactive COPD patients with severe airflow obstruction, suggesting that physical activity may attenuate the progression of vascular dysfunction in COPD 40 . Vaes et al 41 also www.nature.com/scientificreports/ demonstrated a significant association between reduced maximal aerobic capacity (VO 2 peak) and impaired peripheral endothelial function in patients with stable COPD. In this way, our findings revealed significant associations between exercise capacity and endothelial function in severe acute exacerbation of COPD.…”
Section: Exercise Capacity and Endothelial Function In Aecopdmentioning
confidence: 94%